A respiration-detective graphene oxide/lithium battery. Issue 48 (28th November 2016) - Ye, Minghui; Cheng, Huhu; Gao, Jian; Li, Changxia; Qu, Liangti
Abstract : A self-powered and respiration-detective Li–GOF battery is prepared to both supply electricity and detect human respiration in real time. Abstract : Typical lithium ion batteries can only supply electricity, but not detect human respiration at the same time. Herein, we report a self-powered and respiration-detective battery via the simple assembly of Li foil and a graphene oxide film (GOF) without additional electrolytes. In the Li–GOF battery, the GOF can rapidly capture and transfer the moisture originating from the exhaled gas. Meanwhile, Li foil serves as a micro-reactor to trigger the redox reaction between lithium and adsorbed moisture (2Li + 2H2 O = 2LiOH + H2 ). The produced electrons flowing in an external circuit can reflect the rate and depth of respiration in real time. As an extra-power-free device, the respiration-detective Li–GOF battery can supply a specific capacity of 36.4 mA h cm −2, which is ca. 36 times higher than that of conventional lithium ion batteries. Interestingly, the battery can reversibly control the on/off of a light emitting diode by adsorbing/desorbing moisture, respectively. Even if submerged in water, the Li–GOF battery can light up a LED in water for over 1 hour, which can be applied for submarine search and rescue. Beyond this, the Li–GOF battery provides a new platform and allows the construction of a similar hybrid structure for various functions.